Indoor Location Using Ultrasounds - Albuquerque, Daniel (2013)
This thesis presents a location system based exclusively on ultrasonic signals, without using any other technology. This location system was designed to operate in environments where the use of other technologies is not possible or the use of them is limited, such as underwater applications or hospital environments. The proposed location system uses a network of fixed beacons allowing the mobile stations to locate. Due to the necessity of data transmission and distance measurement an ultrasonic pulse robust to echoes was developed that allows to perform both tasks with success. The location system allows that mobiles locate themselves only listening to the information in the ultrasonic pulse sent by the beacons, for that an algorithm based on time difference of arrival is used. Therefore, the user privacy is guaranteed as well as the complete independence of the system number of users. To simplify the network implementation it is only necessary to manually define the position of some of the beacons, called anchor beacons. These will allow the remaining autonomous beacons to locate themselves by an iterative location algorithm based on a local cost function minimization. For this system to work properly the beacons must synchronize their clocks and measure the distance between them. Therefore, this thesis proposes a clock synchronization protocol which also allows to measure the distance between the beacons by exchanging only three ultrasonic messages. Additionally, the location system permits that damaged beacons may be replaced without compromising the network operability reducing the maintenance complexity. Additionally, a simplified ultrasonic simulator for indoor environments was developed, which has proved to be very accurate and a valuable tool to simulate the location system behavior under controlled conditions.